ATRIAL FIBRILLATION RISK IN OUT-PATIENTS WITH CARDIAC PACEMAKERS, IMPLANTED DUE TO ATRIOVENTRICULAR BLOCK - A. P. Ivanov; I. A. Elgardt; O. K. Anya; D. V. Dedov (Российский кардиологический журнал, 2010)
To indentify the predictors of atrial fibrillation (AF) in patients with implanted artificial pacemakers (IPM), 65 such patients were followed up for 6 months. The AF group included 18 (27,7%) patients, while the comparison group consisted of 47 AF-free individuals. AF risk markers included increased maximal length and dispersion of P wave at electrocardiography, as well as increased P wave dispersion (by 13,9%) during the follow-up. In addition, volume, but not linear, characteristics of left atrium (LA) were 1,44-1,77 times greater in AF patients than in AF-free participants. During the follow-up period, linear LA parameters increased regardless of AF (by 19.8% and 14,8%, respectively), while AF volume significantly increased in AF individuals exclusively, which pointed to structural LA remodelling, and not only LA dilatation.